The Effect of Teachers’ Commitment on School Violence Reduction in Secondary Schools in Cameroon - Che, Juliana Ngwe; Saidou, Baba Oumar; Kenmegni, Noumigue Guy Roland (Society & Sustainability, 2024)
A learning environment that fosters creativity among students, educators, parents, and other stakeholders to overcome obstacles to better decision-making and teamwork. This paper was set forth to examine the effect of teachers’ commitment on school violence reduction in secondary schools in Cameroon. This study employed a quantitative research paradigm using a descriptive survey design to gather data through a structured questionnaire comprising 52 closed-ended items. The target population included secondary school students in Cameroon, with a sample size of 301 students selected via simple random sampling from four regions. Data analysis involved descriptive and inferential statistics, utilizing the Seemingly Unrelated Regression (SUR) estimation technique. The findings revealed that teachers’ commitment exerts a significant negative influence on school violence reduction in sampled secondary schools in Cameroon. Specifically, increased teachers’ commitment significantly reduces physical and psychological violence among students of secondary schools in the country. Based on the findings, it is observed that educational authorities must prioritize comprehensive teacher training programs focused on violence prevention and intervention strategies, supported by adequate resources, clear guidelines, and a supportive work environment that enhances teacher commitment and effectiveness in addressing school violence.